Enantiospecific mirror-imaged growth in overlayers of enantiopure thiadiazole-[9]helicene on Au(111) without commensurability - Fumi Nishino; Keisuke Fukutani; Jonas Brandhoff; Marco Gruenewald; Elise Fuerch; Maximilian Schaal; Felix Otto; Daniel Stelter; Roman Forker; Zheng Zhang; Takashi Hirose; Torsten Fritz; et al. (Applied Physics Express)
Two-dimensional (2D) crystallization of chiral molecules on achiral crystal surfaces typically exhibits mirror-imaged growth, defined by the substrate’s mirror plane and the lattices of each enantiomer. While various commensurate molecular overlayers have shown such growth, the possibility of achieving substrate-defined enantiospecific structures in non-commensurate chiral molecular overlayers remains elusive. Here, enantiopure thiadiazole-[9]helicene on Au(111) is shown to form overlayers without commensurability, exhibiting substrate-defined mirror-imaged growth. This study experimentally demonstrates that rotational orientation locking without 2D interface potential minima can support mirror-imaged growth, suggesting that it can serve as a benchmark for enantiospecific growth in a broader range of chiral molecular systems.